Operationalizing One Health in pastoralist settings: Training of One Health service providers in Isiolo and Marsabit counties, Kenya - Yussuf, Buke; Odhiambo, A.; Sake, I.S.; Kofo, K.W.; Mwongela, D.; Elema, E.; Mor, Siobhan M. (International Livestock Research Institute, 2025)
A three-day training workshop titled “Operationalizing One Health in pastoral settings: Training of health service providers in Isiolo and Marsabit Counties” was conducted in Marsabit from 5–7 August 2025. The training was organized by the One Health for Humans, Environment, Animals, and Livelihoods (HEAL) project. A total of 37 participants (13 female and 24 male) health service providers were trained.